2014
DOI: 10.1021/nn502975r
|View full text |Cite
|
Sign up to set email alerts
|

Nanogel-Based Immunologically Stealth Vaccine Targets Macrophages in the Medulla of Lymph Node and Induces Potent Antitumor Immunity

Abstract: Because existing therapeutic cancer vaccines provide only a limited clinical benefit, a different vaccination strategy is necessary to improve vaccine efficacy. We developed a nanoparticulate cancer vaccine by encapsulating a synthetic long peptide antigen within an immunologically inert nanoparticulate hydrogel (nanogel) of cholesteryl pullulan (CHP). After subcutaneous injection to mice, the nanogel-based vaccine was efficiently transported to the draining lymph node, and was preferentially engulfed by medul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 38 publications
2
103
0
Order By: Relevance
“…It was reported that cholesteryl pullulan (CHP) nanogels induce tumor regression in some patients with malignant tumors, 29,30 and CD169-positive macrophages in LN sinus captured CHP nanogels and worked as APCs. 31 Thus, lymphatic-targeting materials might be a promising approach to improving vaccine efficacy, and CD169-positive macrophages are now of interest as APCs to which antigens might be efficiently delivered.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that cholesteryl pullulan (CHP) nanogels induce tumor regression in some patients with malignant tumors, 29,30 and CD169-positive macrophages in LN sinus captured CHP nanogels and worked as APCs. 31 Thus, lymphatic-targeting materials might be a promising approach to improving vaccine efficacy, and CD169-positive macrophages are now of interest as APCs to which antigens might be efficiently delivered.…”
Section: Discussionmentioning
confidence: 99%
“…157 In comparison to soluble antigen formulated in Incomplete Freund’s Adjuvant, antigen encapsulated in these hydrogel nanoparticles substantially delayed tumor growth in a cancer therapeutic model. 157 …”
Section: Overcoming Tissue Barriers For Vaccines and Immunotherapiementioning
confidence: 99%
“…These targeted delivery processes enable less toxic and more effective vaccination by controlling drug dose and prolonging antibody immune responses (Hubbell, Thomas, & Swartz, ). Although nanomaterial‐based platforms using micelles (Cui, Osada, Imaizumi, Kataoka, & Nakano, ), liposomes (Demento et al, ; Yuba, Yamaguchi, Yoshizaki, Harada, & Kono, ), nanoparticles (Shima, Akagi, Uto, & Akashi, ; Uto et al, ), and nanogels (Muraoka et al, ; Nochi et al, ) have been successful, several nanomaterials lacks targeting ability to APCs due to the diffusion in the tissues after subcutaneous injection, which may lead to high total drug dose, multiple administration, and poor vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%